Comparative study between the performances of two Islamic indices - Rama Gardika; Ade Banani; Sulistyandari Sulistyandari (Faculty of Economics and Business, Jenderal Soedirman University, 2018)
This study aims to analyze the differences in the performance of FTSE Bursa Malaysia EMAS Shariah (FBMS) in Malaysia and Indonesia Sharia Stock Index (ISSI) in Indonesia by using Sharpe, Treynor, and Jensen ratio. Type of this study is quantitative research by using hypothesis testing and purposive sampling technique. Population in this study is all sharia indices listed on Indonesia Stock Exchange (IDX) and Bursa Malaysia (BM). From the sampling process obtained two indices. These indices are FTSE Bursa Malaysia EMAS Syariah (FBMS) and Indonesia Sharia Stock Index (ISSI). Objects of this study are monthly index returns during the period of July 2012 to June 2012 which amounted to 60 data. Hypothesis testing is intended to determine whether there is significant difference between the performance of FBMS and ISSI on the measurement of Sharpe, Treynor, and Jensen ratio. Test was conducted by using Two Independent Samples t-test. Results showed that there is no significant difference between the performance of FBMS and ISSI on the Sharpe, Treynor, and Jensen ratio. Implication of this study is that the results of this study can be used as a reference for companies in selecting which Islamic index prefer to issue the stock in based on the performance measured using Sharpe, Treynor, and Jensen ratio. Results of this study also can be used as a reference for investors who are interested in investing funds in sharia stocks in Indonesia and Malaysia.